2017
DOI: 10.1371/journal.pone.0184849
|View full text |Cite
|
Sign up to set email alerts
|

Differential cellular responses associated with oxidative stress and cell fate decision under nitrate and phosphate limitations in Thalassiosira pseudonana: Comparative proteomics

Abstract: Diatoms are important components of marine ecosystems and contribute greatly to the world’s primary production. Despite their important roles in ecosystems, the molecular basis of how diatoms cope with oxidative stress caused by nutrient fluctuations remains largely unknown. Here, an isobaric tags for relative and absolute quantitation (iTRAQ) proteomic method was coupled with a series of physiological and biochemical techniques to explore oxidative stress- and cell fate decision-related cellular and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 78 publications
5
17
1
Order By: Relevance
“…Abiotic stresses caused by environmental changes (i.e., nutrient, light, CO 2 , oxygen, temperature, and osmotic) and biotic stresses (i.e., cell age, viral infection, bacterial growth, allelopathic effect, and grazing by heterotrophs) appear to influence the physiology and survival of diatoms, thereby influencing the flow of photosynthetically fixed organic matter (and associated elements) and primary productivity (5)(6)(7). It has been shown that conserved autocatalytic programmed cell death (PCD) in diatoms can be activated by adverse abiotic or biotic stress conditions, such as the limitation of N, P, Si, or Fe, the overproduction of exogenous aldehyde and sterol sulfate, and viral infection (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic stresses caused by environmental changes (i.e., nutrient, light, CO 2 , oxygen, temperature, and osmotic) and biotic stresses (i.e., cell age, viral infection, bacterial growth, allelopathic effect, and grazing by heterotrophs) appear to influence the physiology and survival of diatoms, thereby influencing the flow of photosynthetically fixed organic matter (and associated elements) and primary productivity (5)(6)(7). It has been shown that conserved autocatalytic programmed cell death (PCD) in diatoms can be activated by adverse abiotic or biotic stress conditions, such as the limitation of N, P, Si, or Fe, the overproduction of exogenous aldehyde and sterol sulfate, and viral infection (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Inhibition of StS biosynthesis could significantly delay the initiation of this cell death process and maintain active growth for several days (14). N and P stress could significantly inhibit the growth of S. marinoi (or other diatoms) and initiation of PCD (15,17,(32)(33)(34). For example, Lin et al (15) used a proteomics approach to evaluate the relative protein abundance in Thalassiosira pseudonana under nutrient limitations, and they found that N-limited cells had much stronger stress responses than P-limited cells.…”
mentioning
confidence: 99%
“…Based on the well-accepted method to classify the up-and downregulation using p-value in t-test (Lin et al, 2017;Fountain et al, 2018), peptides with relative abundance < 0.5 (p < 0.01), 0.5-0.83 (p < 0.05), 1.2-2.0 (p < 0.05), and >2.0 (p < 0.01) were designated in the present study to be significantly up-regulated or down-regulated. They were further classified according to the Gene Ontology (GO) function and GO biological process, via the Universal Protein Resource Database 1 (O'Donovan and Apweiler, 2011; Lai et al, 2017) and PSORTdb 3.0.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous works have attempted to unravel the changes in gene expression and mRNA transcription under stress response (Zhou et al, 2016;Kotrade et al, 2019;Qiao et al, 2019;Szabo et al, 2019), evidence has shown poor correlations between transcriptional and protein levels (Pascal et al, 2008). Accordingly, recent studies have employed proteomic analysis to investigate microbial global response to environmental stresses, e.g., antibiotic stress (Mathieu et al, 2016;Xiong et al, 2017), cold and light stress (Liu et al, 2018), oxidative stress (van Herwijnen et al, 2003), drying stress (Schott et al, 2017), thermal stress (Delgado-Baquerizo et al, 2018), and nitrate and phosphate depletion (Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation